6S-1 RNA Contributes to Sporulation and Parasporal Crystal Formation in Bacillus thuringiensis - Li, Zhou; Zhu, Li; Yu, Zhaoqing; Liu, Lu; Chou, Shan-Ho; Wang, Jieping; He, Jin (Frontiers in Microbiology, 2020)
6S RNA is a kind of high-abundance non-coding RNA that globally regulates bacterial transcription by interacting with RNA polymerase holoenzyme. Through bioinformatics analysis, we found that there are two tandem 6S RNA-encoding genes in the genomes of Bacillus cereus group bacteria. Using Bacillus thuringiensis BMB171 as the starting strain, we have explored the physiological functions of 6S RNAs, and found that the genes ssrSA and ssrSB encoding 6S-1 and 6S-2 RNAs were located in the same operon and are co-transcribed as a precursor that might be processed by specific ribonucleases to form mature 6S-1 and 6S-2 RNAs. We also constructed two single-gene deletion mutant strains ΔssrSA and ΔssrSB and a double-gene deletion mutant strain ΔssrSAB by means of the markerless gene knockout method. Our data show that deletion of 6S-1 RNA inhibited the growth of B. thuringiensis in the stationary phase, leading to lysis of some bacterial cells. Furthermore, deletion of 6S-1 RNA also significantly reduced the spore number and parasporal crystal content. Our work reveals that B. thuringiensis 6S RNA played an important regulatory role in ensuring the sporulation and parasporal crystal formation.